Effectiveness of community-based livestock protection strategies: a case study of human-lion conflict mitigation - Sibanda, L; Johnson, PJ; Van Der Meer, E; Hughes, C; Dlodlo, B; Mathe, LJ; Hunt, JE; Parry, RH; Macdonald, D; Loveridge, AJ (Cambridge University Press, 2021)
Conservation scientists are increasingly emphasising the need to evaluate the effectiveness of coexistence interventions across different contexts. In this study, we assessed the long-term efficacy of a community-based programme: the Long Shields Community Guardians. The programme protects livestock and mitigates depredation by lions through non-lethal means with the ultimate aim of promoting human-lion coexistence. Using an experimental approach, we measured temporal trends in livestock depredation by lions as well as the prevalence of retaliatory lion killing by farmers and wildlife managers. Farmers that were part of the Long Shields programme experienced a significant reduction in livestock loss to lions and the number of lions killed annually due to retaliatory killing by farmers dropped by 41% since the start of this programme in 2013, compared to the period 2008-2012 before the programme was initiated. Our results demonstrate the Long Shields programme can be a potential model for limiting livestock depredation by lions elsewhere. More broadly, our study demonstrates the effectiveness of community-based conflict interventions in engaging community responses to livestock protection and ameliorating levels of retaliatory killing, thereby reducing human-lion conflict.